THE IMPLEMENTATION OF A MUSLIM FASHION SHOW IN ISLAMIC RELIGIOUS EDUCATION AT TK IT CEUDAH MULYA - Sari Rizki; Novysa Basri; Siti Nur Balqis (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to assess the implementation of a Muslim fashion show as a teaching tool for Islamic Religious Education (PAI) at Ceudah Mulya Nursery School. The research method employed was a descriptive qualitative approach with a focus on case studies. Data were collected through direct observation, in-depth interviews with the headteacher, teachers and parents, as well as documentation relating to the activity. The results of the study reveal that the organisation of the Muslim fashion show at Ceudah Mulya Islamic Kindergarten was carried out in a structured manner across three stages: planning, implementation, and evaluation. This activity proved effective in instilling the values of modesty, fostering a love for Islamic clothing, and shaping religious character in pre-school-aged children. Furthermore, this activity also had a positive impact on the children’s social-emotional development, gross and fine motor skills, and self-confidence. This study concluded that the Muslim fashion show is a creative learning method that aligns with the principles of experience-based learning within the context of Islamic Education in Early Childhood Education.